2015
DOI: 10.1007/s11605-015-2796-1
|View full text |Cite
|
Sign up to set email alerts
|

Laparoscopic Repair of Paraesophageal Hernias with a Falciform Ligament Buttress

Abstract: Laparoscopic PEH repair with a falciform ligament buttress is a viable option. Ongoing follow-up will demonstrate the utility of this approach to decrease morbidity and recurrence rates for paraesophageal hernia repairs.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(4 citation statements)
references
References 19 publications
0
4
0
Order By: Relevance
“…12 Furthermore, falciform ligament was utilized as a natural biological buttress or mesh hiatoplasty to prevent recurrence during paraesophageal hernia repair. [13][14][15][16] A total of n = 153 patients received falciform ligament for cural closure. All involved studies reported decreased recurrence compared to primary closure, although no comparisons were made with mesh closures.…”
Section: Gastrointestinal Surgerymentioning
confidence: 99%
See 1 more Smart Citation
“…12 Furthermore, falciform ligament was utilized as a natural biological buttress or mesh hiatoplasty to prevent recurrence during paraesophageal hernia repair. [13][14][15][16] A total of n = 153 patients received falciform ligament for cural closure. All involved studies reported decreased recurrence compared to primary closure, although no comparisons were made with mesh closures.…”
Section: Gastrointestinal Surgerymentioning
confidence: 99%
“…Laird and Harr reported a prospective experience of 34 patients, noting that both symptom frequency and severity decreased significantly by 1 year follow-up. 15 Runkel et al reported 78 cases of falciform ligament repair compared to 229 controls, and noted that recurrence was 15% compared to 72% in treatment of concamintant hiatal hernia following bariatric surgery.…”
Section: Gastrointestinal Surgerymentioning
confidence: 99%
“…Currently, the falciform ligament flap is used in pancreatic surgery to reduce postoperative morbidity 23 25 . Moreover, the falciform ligament flap can be applied for laparoscopic repair of the crural defect caused by paraesophageal hernia 26 , 27 .…”
Section: Introductionmentioning
confidence: 99%
“…[3] Radiological recurrence was 15% and symptomatic recurrence was 4%. Grossman and co-workers [8] used a 10 mm camera, a 12 mm trocar, and three 5 mm trocars in their study consisting of 104 cases and they used the falciform ligament to support the primary repair of the hiatal defect, before fundoplication. They reported that this technique was well tolerated with minimal complications, and radiological recurrence rate was %8.8 in one year follow up.…”
mentioning
confidence: 99%